Analisis Permintaan Buah Pisang Di Kota Denpasar, Bali - PK Suparyana; W Ramantha; W Budiasa (JURNAL MANAJEMEN AGRIBISNIS, 2017)
ABSTRACTDemand Analysis For Bananas In Denpasar CityThis study aims at finding out factors influencing demand for bananas andcalculating price, income and cross elasticies of demand for bananas in Denpasar. Thestudy focuses on household consumers in Denpasar City including 100 respondents.Data were analyzed using multiple linear regression considering economic,econometrics and statistics criteria.Based on the linear regression analysis, the demand model for bananas inDenpasar is lnY = -43,156 -0,139 lnX1 -0,600 lnX2 -0,378 lnX3 +5,896 lnX4 +0,776lnX5 +3,365 lnX6 +0,418 lnX7 +0,548 lnD. All independent variables aresimultaneously significant affecting demand for bananas in Denpasar. Partially, pricesof zalacca, rambutan, total income, number of household members, and purpose ofpurchasing significantly affecting demand for bananas. Meanwhile, price of bananas,price of oranges, and price of mangoes do not have significant effect on demand forbananas. Price elasticity of demand for bananas shows an inelastic figure (e<1),implying that demand for bananas is not responsive to the price changes. A positive signin the value of the income elasticity indicates that banana is a normal good. Sign of thecross-price elasticity of oranges and mango prices was negative, referring that thesefruits are complementary to bananas. On the other hand, cross-price elasticities ofzalacca and rambutan are positive, meaning that zalacca and rambutan are substitutecommodities to bananas.Keywords: demand for bananas, regression, elasticity, household, Denpasar